The Etruscans a very short introduction - Smith, Christopher 1965- (Very short introductions, 2014)
The Etruscans (c. 900-400 BC) were a highly sophisticated and wealthy elite. Christopher Smith explores their archaeological record and the myths that remain about their existence. Placing the Etruscans within the context of the historical period and geographical location, he looks at how they have been perceived and received throughout history